REFUEL: An EU road map for biofuels - Londo, M.; Deurwaarder, E.; Lensink, S.; Fischer, G.; Prieler, S.; van Velthuizen, H.; de Wit, M.; Faaij, A.; Berndes, G.; Hansson, J.; Duer, H.; Lundbaek, J.; et al. (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
A successful mid-term development of biofuels calls for a robust road map. REFUEL assesses inter alia least-cost biofuel chain options, their benefits, outlines the technological, legislative and other developments that should take place, and evaluate different policy strategies for realisation. Based on preliminary results some preliminary conclusions of the project are discussed here. There is a significant domestic land potential for energy crops in the EU, which could supply between one quarter and one third of gasoline and diesel demand by 2030 if converted into advanced biofuels. A biomass supply of 8 to 10 EJ of primary energy could be available at costs around or below 3 €/GJ. However, the introduction of advanced biofuel options may meet a considerable introductory cost barrier, which will not be overcome when EU policy is oriented to the introduction of biofuels at least cost. Therefore, conventional biodiesel and ethanol may dominate the market for decades to come, unless biofuels incentives are differentiated, e.g. on the basis of the differences in greenhouse gas performance among biofuels. The introduction of advanced biofuels may also be enhanced by creating stepping stones or searching introduction synergies. A stepping stone can be the shortterm development of lignocellulosic biomass supply chains for power generation by cofiring; synergies can be found between advanced FT-diesel production and hydrogen production for the fuel cell.